Blockchain and Emerging Distributed Ledger Technologies for Decentralized Multi-robot Systems - Peña Queralta, Jorge; Keramat, Farhad; Salimi, Salma; Fu, Lei; Yu, Xianjia; Westerlund, Tomi (Springer, 2025)
Purpose of Review: Distributed ledger technologies (DLTs), particularly blockchain, are paving the way to securing and managing distributed and large-scale systems of autonomous agents. We look into how these technologies are moving out of the lab and into the real world within the robotics field.
Recent Findings: Despite the scalability and real-world applicability concerns, new solutions have emerged that show resilience to intermittent connectivity, as well as scalable solutions for managed or permissioned networks.
Summary: We present a review on the various use cases that different DLTs can support in multi-robot systems. We argue that the majority of the work to date on open and permissionless blockchains is only applicable to a subset of robotics use cases, with novel DLT architectures and permissioned blockchains driving adoption across industrial and more mature application scenarios.
Keywords Blockchain · Multi-Robot systems · Auditability · Autonomy · Distributed ledger technologies · Ethereum · Hyperledger fabric · IOTA